Exposure to violence and the presence of suicidal and self-harm behaviour predominantly in Asian females: scoping review - Sheikh Shoib; Sonia Khan; Alaa Baiou; Miyuru Chandradasa; Sarya Swed; Serkan Turan; Aishatu Yusha’u Armiya’u (Middle East Current Psychiatry, 2022)
Abstract Background Exposure to violence is associated with psychological distress, mental disorders such as depression, and suicidal behaviour. Most of the studies are conducted in the West, with limited publications from Asia. Thus, we conducted a scoping review of studies investigating the association between experiences of violence and later suicidal ideation/attempts from Asia in the twenty-first century. Results Many studies focused on domestic violence toward women in the Southeast Asian region. Sociocultural factors such as family disputes, public shaming, dowry, lack of education opportunities, and marriage life perceptions mediated the association. Many women exposed to violence and attempted suicide suffered from mental disorders such as depression, anxiety, and post-traumatic stress. The small number of suitable studies and the possible effect of confounders on participants were limitations in the review. Future studies would have to focus on specific types of violence and ethnoreligious beliefs. Conclusion Women in Asia exposed to violence appear to have an increased risk of suicidal behaviour and mental disorders. The early screening of psychological distress with culturally validated tools is essential for preventing suicides in Asian victims of violence.